Georgia : Technical Assistance Report-Scanner Data for CPI. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
The purpose of the mission was to assist the National Statistics Office of Georgia (Geostat) with continuing its modernization of the Consumer Price Index (CPI). This was the first technical assistance (TA) mission to Georgia to specifically focus on scanner data (SD). Two earlier missions on the residential property price index (RPPI) (September 23-October 4, 2019, and November 30-December 4, 2020) already provided initial guidance and addressed the planned modernization of the CPI using SD. The mission was delivered remotely, and the sessions were recorded for future reference.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Georgia